ЕНЕРГЕТИЧНІ ХАРАКТЕРИСТИКИ РЕЗОНАНСНОГО КОНВЕРТОРА З ДОЗОВАНОЮ ПЕРЕДАЧЕЮ ЕНЕРГІЇ - Волков, І.В.; Подольний, С.В. (Інститут електродинаміки НАН України, Київ, 2021)
This article investigated two cases of impulse transformer location selection in the DC-DC type two-step resonant converter, which fully segregates processes of taking and transferring energy between the input and its load. The electromagnetic processes during energy taking/transferring were studied, including active and static losses in the converter elements. Based on the suggested analytical-numerical method, the criteria for selecting the impulse transformer optimal transformation ratio, from the system efficiency point of view, was derived. The proposed optimization technique can be applied to a wide variety of input and output parameters. References 3, Figures 7.